Household Cooking Fuel Choice in India, 2004-2012: A Panel Multinomial Analysis - Ying-Min Kuo; Mehtabul Azam (Institute of Labor Economics (IZA), 2019)
We use two waves of nationally representative India Human Development Survey to examine factors driving the cooking fuel choice in urban and rural India, separately. We utilize a random effects multinomial logit model that controls for unobserved household heterogeneity. We find that a clean-break with the use of traditional fuels is less likely in rural areas, but more probable in urban areas. The household characteristics (e.g. income, education) that are positively correlated with use of clean fuel also increases the probability of fuel stacking for rural households. We also find that access to paved road is an important determinant for rural household adopting clean fuel, and there exists evidence of social spillover effects in rural areas. Moreover, the bargaining power of women that is associated with economic status (e.g. education or economic freedom) is positively associated with the use of clean fuel. Finally, we find considerable impact of liquefied petroleum gas prices on the probability of use of clean fuel for urban households, but no significant impact for rural households.
Keywords: Q42; Q35; O12; O13; C25; 330; fuel choice; fuel stacking; random eects multinomial logit; India